Nubdzah fi Radd Ahl Al-Tariqah fi Singapura oleh Salim Ibn Sumair: Sebuah Komentar Terhadap Penganut Tarekat di Nusantara Abad 19 - Arifin Arifin (Jumantara: Jurnal Manuskrip Nusantara, 2022)
The history of Islam in the archipelago, especially since the early 17th to 19th centuries, has produced a number of religious texts that are quite large, including various kinds of texts from several Islamic disciplines. Now these manuscripts can be used as primary sources for writing the intellectual and social history of Islam in the archipelago. Among the several topics from these manuscripts are those relating to criticism of the tarekat teachings in the archipelago, especially in the bidding of the tarekat without paying attention to the conditions for following the tarekat. One of them is basic understanding such as the science of monotheism and Islamic law. This article aims to explain the dynamics of tarekat sufism in the archipelago from the 17th to the early 19th centuries, and what are the reasons for the criticisms carried out by interpreters of Islam in parts of the archipelago. The primary object of this article is the manuscript Nubdhah fi Radd Ahl al-Tarikat fi Singapura, which is a religious work devoted to straightening sufi teachers and tarekah adherents who recruit their congregations without considering the conditions that have been quoted by sufi scholars. In analyzing the manuscript, this article uses the Paratex Gerade Genete theory by looking for the elements that accompany the text, both those contained in the manuscript or outside the manuscript.